2006
DOI: 10.1111/j.1365-2133.1985.tb15264.x
|View full text |Cite
|
Sign up to set email alerts
|

The value of bacteriology and serology in the diagnosis of cellulitis and erysipelas

Abstract: Patients diagnosed as suffering from erysipelas or cellulitis were subjected to bacteriological and serological investigations. The serological tests used included the anti-streptolysin O reaction (ASO), the anti-deoxyribonuclease B test (ADB) and the anti-hyaluronidase tests (AHT) that are specific both for the group A streptococcus (Streptococcus pyogenes) and for the human pyogenic streptococci of group C or group G. Antibody tests to the 3!-lysin and the nuclease of Staphylococcus aureus were also employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(30 citation statements)
references
References 10 publications
0
27
0
3
Order By: Relevance
“…This was in concordance with the findings of Erikson B et al in which beta haemolytic streptococci were detected in 34% of the patients. (15,16) Fifty patients with cellulitis were prospectively evaluated by Edward W Hook III et al and made similar conclusions (17) . Beta haemolytic streptococci were isolated from 17 primary lesions and coagulase positive staphylococci from 13 primary lesions.…”
Section: Discussionmentioning
confidence: 88%
“…This was in concordance with the findings of Erikson B et al in which beta haemolytic streptococci were detected in 34% of the patients. (15,16) Fifty patients with cellulitis were prospectively evaluated by Edward W Hook III et al and made similar conclusions (17) . Beta haemolytic streptococci were isolated from 17 primary lesions and coagulase positive staphylococci from 13 primary lesions.…”
Section: Discussionmentioning
confidence: 88%
“…This study used a combination of PCR from skin swabs, skin swab culture, throat swab culture and serology to detect evidence of GAS or S. aureus in clinical cases of cellulitis; other studies have used immunofluorescence of skin biopsies (Bernard et al, 1989), PCR of tissue aspirates (Johnson et al, 2012) and serology (Jeng et al, 2010;Karppelin et al, 2014;Leppard et al, 1985). Despite this wide repertoire of testing, we were unable to achieve a confirmed bacteriological diagnosis in as many patients as those using serology alone.…”
Section: Discussionmentioning
confidence: 99%
“…Using all 3 tests, 1 study found serologic evidence of recent streptococcal infection in 24 of 28 patients (86%) in patients with lower limb cellulitis. 55 In an investigation confined to ''nonculturable'' cellulitis, primarily affecting the legs, ASO and/or ADB titers indicated recent streptococcal infection in 70% of cases and, when joined with information from blood cultures, implicated streptococci as the cause of cellulitis in 73% of the patients. 2 A study of lower extremity cellulitis used immunofluorescent staining for streptococcal antigens of groups A, C, D, and G in skin biopsy specimens, along with ASO and ABD titers.…”
Section: Predisposing Factors Key Pointsmentioning
confidence: 98%
“…44,47,48,53 The results of cultures from needle aspirations of intact but inflamed skin are remarkably disparate in various studies, with rates of positivity ranging from \5% to about 40%. 28,39,44,45,49,50,52,[54][55][56][57][58][59][60][61] The differences probably relate to the types of populations investigated, discrepant definitions of cellulitis, the presence or absence of patients with associated abscesses, the frequency of immunocompromised hosts, and the decision about whether isolates are pathogens or contaminants. Most patients in these studies had lower limb cellulitis, but some had infection elsewhere, such as the upper extremities.…”
Section: Predisposing Factors Key Pointsmentioning
confidence: 99%